2021
DOI: 10.1002/ajb2.1686
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeographic history of a range disjunction in eastern North America: the role of post‐glacial expansion into newly suitable habitat

Abstract: PREMISE A disjunct distribution, where a species’ geographic range is discontinuous, can occur through vicariance or long‐distance dispersal. Approximately 75 North American plant species exhibit a ~650 km disjunction between the Ozark and Appalachian regions. This disjunction is attributed to biogeographic forces including: (1) Eocene–Oligocene vicariance by the formation of the Mississippi embayment; (2) Pleistocene vicariance from interglacial flooding; (3) post‐Pleistocene northward colonization from separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…ENM has also been used to identify past glacial refugia (Waltari et al, 2007 ). One example of how ENM can help infer the phylogeographic history of a group is illustrated in a study of Delphinium exaltatum (Mohn et al, 2021 ), where ENM analyses indicated that a divergence occurred due to postglacial northward range expansion. ENM also helped narrow estimates of the divergence time between the two lineages by showing that one lineage showed a major shift in niche availability over a 500‐year period; this gap in niche space would have required very rapid migration rates for this lineage, suggesting that it likely did not exist prior to the shift in niche availability.…”
Section: Discussionmentioning
confidence: 99%
“…ENM has also been used to identify past glacial refugia (Waltari et al, 2007 ). One example of how ENM can help infer the phylogeographic history of a group is illustrated in a study of Delphinium exaltatum (Mohn et al, 2021 ), where ENM analyses indicated that a divergence occurred due to postglacial northward range expansion. ENM also helped narrow estimates of the divergence time between the two lineages by showing that one lineage showed a major shift in niche availability over a 500‐year period; this gap in niche space would have required very rapid migration rates for this lineage, suggesting that it likely did not exist prior to the shift in niche availability.…”
Section: Discussionmentioning
confidence: 99%
“…laciniata is that it is an artifact of the particular microsatellite markers developed for this study, possibly related in some way to how we isolated the microsatellite loci. However, we employed well-established marker-development protocols that we have used successfully to identify polymorphic microsatellites in a wide diversity of plant species (Swift et al, 2016;Edwards et al, 2019Edwards et al, , 2021Mohn et al, 2021). Furthermore, while developing the markers, we attempted to avoid ascertainment bias by incorporating material from multiple maternal individuals of L. exigua var.…”
Section: Genetic Diversity and Mating System In Leavenworthia Exigua ...mentioning
confidence: 99%
“…However, SDMs rely on numerous assumptions, including temporal stability of species' niches, and the absence of both dispersal constraints and species interactions (Wiens et al., 2009). Finally, genetic data can help infer population histories (Hu et al., 2009; McLachlan et al., 2005; Mohn et al., 2021), including timing of population splits and distinct migration pathways (Avise, 1992; Laricchia et al., 2015; Shafer et al., 2010). Nevertheless, genetic inferences suffer from identifiability issues.…”
Section: Introductionmentioning
confidence: 99%